How to Evaluate Health-Related Quality of Life and Its Association with Medication Adherence in Pulmonary Tuberculosis – Designing a Prospective Observational Study in South Africa - Kastien-Hilka, Tanja; Rosenkranz, Bernd; Bennett, Bryan; Sinanovic, Edina; Schwenkglenks, Matthias (Frontiers in Pharmacology, 2016)
Introduction: Health-related quality of life (HRQOL) has become an important measure to identify and shape effective and patient-relevant healthcare interventions innovations through outcomes. Adherence to tuberculosis (TB) treatment is a public health concern. The main objective of this research is to develop a study design for evaluation of HRQOL and its association with medication adherence in TB in South Africa. Methodology: A conceptual framework for HRQOL in TB has been developed to identify patient-reported outcome (PRO) measures for HRQOL and adherence and to generate an endpoint model. Two generic (SF-12 and EQ-5D-5L), one disease-specific (St. George´s Respiratory Questionnaire (SGRQ)) and one condition-specific (Hospital Anxiety and Depression Scale (HADS)) measure for HRQOL and Morisky Medication Adherence Scale (MMAS) for adherence assessment were identified. All measures are applied in a longitudinal multicentre study at five data collection time points during standard TB treatment. Statistical analysis includes multivariable analysis. Change over time in the physical component score (PCS) of SF-12 is defined as primary endpoint. Sample size estimation based thereupon has led to a recruitment target of 96 patients. This study is on-going. Discussion: This is the first longitudinal study in South Africa which evaluates HRQOL and its association with medication adherence in TB in a comprehensive manner. Results will help to improve current treatment programmes and medication adherence and will support the identification of sustainable health innovations in TB, determining the value of new products, and supporting decision making with regard to health policy and pricing.